Detection of tick-borne pathogens in blood-fed ticks from animals across nine Asian countries - Hye-Ryung Byun; Mi-Sun Rieu; Seong-Ryeong Ji; Hyun-Young Nam; Seulgi Seo; Chang-Yong Choi; Bui Khanh Linh; Hien Le Thanh; Morakot Kaewthamasorn; Ana Sahara; Remil L. Galay; Shang-Lin Wang; et al. (Microbiology Spectrum)
ABSTRACT Climate change, land development, and increased outdoor human activity have increased the prevalence and distribution of tick-borne pathogens, causing public health issues. Asia is a pivotal region of emerging infectious diseases caused by zoonotic disease. Therefore, this study aimed to construct effective surveillance systems and establish preventive strategies against novel tick-borne diseases. Next-generation sequencing (NGS) was performed to detect tick-borne pathogens from animal blood-fed ticks. Ticks (n = 261) were collected from different animals across nine Asian countries between 2022 and 2023. Five genera of adults and nymphal ticks were used, namely, Amblyomma, Haemaphysalis, Hyalomma, Rhipicephalus, and Ixodes. The animals from which the ticks were collected were wild, domestic animals, birds, and reptiles, living in the natural environment. After NGS, clean reads of 18,382,262–30,460,619 DNA viruses, 22,744,384–32,400,471 RNA viruses, 134,506–286,282 16S rRNA of bacteria, and 147,154–352,826 18S rRNA of protozoa were obtained from nine Asian countries. After analysis of the species, 28 RNA, 13 DNA viruses, 16 bacteria, and 4 protozoa were detected. Several tick-borne pathogens, including those in families that cause zoonotic diseases, such as Phenuiviridae, Nairoviridae, Rickettsiaceae, and Borreliaceae, were identified. This study is distinctive in that it involved cooperative studies with nine Asian countries to prevent the spread of tick-borne diseases. The results suggest that pathogens, which were detected in animal blood-fed ticks, can circulate in animals and may be transmitted to humans. In addition, this study can provide a basis for effective surveillance systems to prevent novel pathogens.IMPORTANCESurveillance systems against novel tick-borne diseases are significant for global health. Climate and other environmental changes have contributed to an expanding range of ticks and tick-borne diseases. Areas in Asia constitute key areas of emerging infectious diseases. Through analysis of blood-fed ticks, collected from various animals living in the natural environment, we suggest that tick-borne pathogens may harbor animals and environment and have potential risk of transmission in humans. Understanding the distribution of tick-borne pathogens requires cooperative studying and, thus, can construct standardized surveillance systems.